Potent inhibitors of malarial P. Falciparum protein kinase G: Improving the cell activity of a series of imidazopyridines. Issue 3 (1st February 2019) - Large, Jonathan M.; Birchall, Kristian; Bouloc, Nathalie S.; Merritt, Andy T.; Smiljanic-Hurley, Ela; Tsagris, Denise J.; Wheldon, Mary C.; Ansell, Keith H.; Coombs, Peter J.; Kettleborough, Catherine A.; Whalley, David; Stewart, Lindsay B.; et al.
Graphical abstract: Abstract: Development of a class of bicyclic inhibitors of the Plasmodium falciparum cyclic GMP-dependent protein kinase ( Pf PKG), starting from known compounds with activity against a related parasite PKG orthologue, is reported. Examination of key sub-structural elements led to new compounds with good levels of inhibitory activity against the recombinant kinase and in vitro activity against the parasite. Key examples were shown to possess encouraging in vitro ADME properties, and computational analysis provided valuable insight into the origins of the observed activity profiles.